Cultural Diversity and Early Education - A Comparison of Educational Approaches in Different Cultural Contexts - Xia, Ning (Transactions on Social Science, Education and Humanities Research, 2024)
This paper explores the impact of cultural diversity on early education, using China and Australia as examples for comparative analysis. Differences in educational theory and practice in cultural contexts are first described, including educational goals, teaching methods, family involvement and assessment approaches. It then explores the long-term effects of culture on children's cognitive, social and emotional development. It was found that China focuses on academic achievement and collective values, while Australia emphasises individual creativity and holistic development. Finally, recommendations were made to promote intercultural educational practices, including educational diversity understanding, home-school community collaboration, flexible assessment and intercultural communication.